EXPLORATION OF GREEN ENVIRONMENTAL PRO-BEHAVIOR OF FISIP STUDENTS, UNIVERSITY OF LAMPUNG - Nina Yudha Aryanti; Astiwi Inayah, Rahayu Lestari (Adisam Publisher, 2025)
Complex environmental problems due to global warming are problems that have a negative impact on human life. One of the preventive efforts that can be done is by inviting universities to reduce the impact of global warming through the implementation of green metric programs on campus. This study aims to determine and analyze how much the tendency of FISIP University of Lampung students' behavior is in behaving environmentally friendly. This study uses a quantitative descriptive method. The respondents of this study were FISIP University of Lampung (Unila) students. The instruments and data analysis used pro-environmental theory and UI Greenmetric guidelines. The results of the study showed that the average student response to green environmental behavior in FISIP Unila students was 6 green metric indicators: Setting & Infrastructure (71.46%), Energy and Climate Change (65.03%), Waste (71.70%), Water (70.35), Transportation (70.56%), and Education/daily activities on campus related to the green environment (40.38%).